SISTEM PENGELOLAAN SURAT PADA DINAS PERHUBUNGAN KOTA BENGKULU - Sabella Azhari; Jian Maheksa; Devano Checario; Andrean Ranata; M.Muslimin (Kohesi: Jurnal Sains dan Teknologi, 2025)
The Bengkulu City Transportation Agency is an important part of the local government responsible for regulating transportation in the Bengkulu City area. In carrying out its duties, the Bengkulu City Transportation Agency faces challenges in quite complicated letter administration. Therefore, an effective and efficient letter management system is needed to support smooth operations. This study aims to examine the letter management system used in the Bengkulu City Transportation Agency, find existing obstacles, and provide suggestions for improvements to improve letter management performance. Currently, the process of managing incoming and outgoing letters in many agencies, from receiving, creating, storing, to documenting, is still done manually. With the existence of a web-based incoming and outgoing letter information system, it is expected to reduce the difficulty in storing and searching for letter documents. The time needed to find letter data will be shorter, and the management of existing letter archives will be better. This letter information system was developed using the waterfall model. Dishub Kota Bengkulu adalah bagian penting dari pemerintah daerah yang bertanggung jawab atas pengaturan transportasi di wilayah Kota Bengkulu. Dalam pelaksanaan tugasnya, Dishub Kota Bengkulu menghadapi tantangan dalam administrasi surat yang cukup rumit. Oleh karena itu, diperlukan sistem pengelolaan surat yang efektif dan efisien untuk mendukung operasional yang lancar. Penelitian ini bertujuan untuk menelaah sistem pengelolaan surat yang digunakan di Dishub Kota Bengkulu, menemukan kendala yang ada, dan memberikan saran perbaikan untuk meningkatkan kinerja pengelolaan surat. Saat ini, proses pengelolaan surat masuk dan keluar di banyak instansi, mulai dari penerimaan, pembuatan, penyimpanan, hingga pendokumentasian, masih dilakukan secara manual. Dengan adanya sistem informasi surat masuk dan keluar berbasis web, diharapkan dapat mengurangi kesulitan dalam penyimpanan dan pencarian dokumen surat. Waktu yang dibutuhkan untuk menemukan data surat akan lebih singkat, dan pengelolaan arsip surat yang ada akan lebih baik. Sistem informasi surat ini dikembangkan menggunakan model waterfall.